Spore 191: Scaling - A high priority for agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
Agricultural innovations must have a more substantial impact to meet the United Nation’s Sustainable Development Goals (SDGs) by 2030 – which call for a concerted effort from the public and private sectors, as well as farmers and processors.